STUDI EKSPERIMENTAL PERPINDAHAN PANAS DAN PENURUNAN TEKANAN DARI HIBRIDA NANOFLUIDA DI PENDINGIN RADIATOR MOBIL - Ery Diniardi; Hasan Basri; Anwar Ilmar Ramadhan; Deni Almanda; Alvika Meta Sari (Jurnal Teknologi, 2022)
The use of nanoparticle coolants in car radiators increases the rate of heat transfer and allows for a smaller overall radiator size. The transfer characteristics of hybrid nanofluids with various compositions of TiO2-SiO2 (40:60, 60:40, 80:20) based water/EG nanoparticles for a volume concentration of 1.0% were investigated experimentally. By dispersing the hybrid nanofluids in a mixture of water/ethylene glycol (60:40), the composition of the TiO2-SiO2 nanoparticles (40:60, 60:40, 80:20) was varied for a volume concentration of 1.0%. Experiments were carried out using a coolant flow rate between 2-12 LPM for a working fluid temperature of 70 °C, while the air flow velocity remained constant at an average of 4 m/s, to understand the effect of coolant flow velocity on heat transfer. The thermal performance of hybrid nanofluids in a water/EG mixture (60:40) was investigated for variations in the composition of TiO2-SiO2 nanoparticles (40:60, 60:40, 80:20) for a volume concentration of 1.0% and a working temperature of 70 °C. The heat transfer coefficient obtained is 32.1%, the maximum increase occurs in the TiO2-SiO2 nanofluid with the composition (40:60), while the 29.2% increase occurs in the nanofluid hybrid (60:40), for the nanofluid hybrid (80:20) it is an increase of 31.1%.